Performance Studies of Proton Exchange Membrane Fuel Cells with Different Flow Field Designs – Review - Marappan, Muthukumar; Palaniswamy, Karthikeyan; Velumani, Thiagarajan; Chul, Kim Byung; Velayutham, Rajavel; Shivakumar, Praveenkumar; Sundaram, Senthilarasu (Chemical record, 2021)
Proton Exchange Membrane Fuel Cell (PEMFC) is majorly used for power generation without producing any emission. In PEMFC, the water generated in the cathode heavily affects the performance of fuel cell which needs better water management. The flow channel designs, dimensions, shape and size of the rib/channel, effective area of the flow channel and material properties are considered for better water management and performance enhancement of the PEMFC in addition to the inlet reactant's mass flow rate, flow directions, relative humidity, pressure and temperature. With the purpose of increasing the output energy of the fuel cell, many flow field designs are being developed continuously. In this paper, the performance of various conventional, modified, hybrid and new flow field designs of the PEMFC is studied in detail. Further the effects of channel tapering, channel bending, landing to channels width ratios, channel cross‐sections and insertion of baffles/blockages/pin‐fins/inserts are reviewed. The power density of the flow field designs, the physical parameters like active area, dimensions of channel/rib, number of channels; and the operating parameters like temperature and pressure are also tabulated. Flow fields are the important component of Proton Exchange Membrane Fuel Cell (PEMFC) Many design modifications have been carried out on the conventional flow field designs and Noval flow field designs have been developed with insert technology to improve the performance of PEMFC. The various flow field designs and their design and operating parameters along with the power output are highlighted. The clamping pressure is also affecting the performance of PEMFC.